Personality of The Main Character in Inside Out Movie Directed by Pete Docter - Wa Ode Zaltina; Rasiah Rasiah; Nur Israfyan Sofyan (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This thesis aims to analyze the personality of the main character reflected in the movie Inside Out by Pete Docter using Sigmund Freud's psychoanalysis studies. This research uses descriptive qualitative research methods. The data source in this study is Inside Out movie which is directed by Pete Docter, as well as articles, books, and theses that can provide information related to this research. Data is collected through watching, taking notes, taking pictures, and identifying. The results showed that in the main character there is Id, Ego, and Superego. Next as in the new students, there will be a directive from the teacher that we must introduce ourselves first so that we can be known in our environment that's what Riley did when entering a new school in San Francisco. Also for the sake of hobbies and support from her parents, he had to rise from the slump and he began to adapt well to her new neighborhood of San Francisco. In this case, the most guided in the main character is compassion, attention, and unyielding. Keywords: Movie, personality, psychoanalysis.